Ethical issues in HIV prevention research with people who inject drugs. (April 2014) - Sugarman, Jeremy; Rose, Scott M; Metzger, David
Background: Injection drug use continues to significantly contribute to new infections with HIV. Moreover, conducting HIV prevention research with people who inject drugs (PWIDs) can be complicated for an array of practical, social, legal, and ethical reasons. It is critical that these research efforts are sensitive to the particular vulnerabilities associated with injection drug use as well as those related to being at risk of acquiring HIV so as to minimize harm to participants in research. Purpose: To describe how we addressed some of these ethical challenges during the course of a large-scale multinational randomized HIV prevention trial involving PWIDs, which was successfully completed. Methods: The ethical issues encountered during the life cycle of the trial were cataloged by the principal investigator, study coordinator, and ethicist working on the trial. Relevant study documents were then reviewed to provide pertinent details. The ethical issues unique to the trial were then described. Results: Before implementation, the trial faced particularly complex challenges related to the vulnerability of PWIDs, where HIV seroincidence rates in the population were high and legal policies and stigma regarding injection drug use was severe. Accordingly, a rapid policy assessment was commissioned, and a series of community engagement activities were conducted. During the trial, in addition to using careful standard operating procedures regarding all aspects of trial conduct and extensive staff training, the trial standardized informed consent procedures and assessed them. Furthermore, social harms were monitored along with physical harms and adverse events. Following the decision to close the study, it was critical to develop an orderly and safe process for closing it. The issue of post-trial access to the study medication and a complex intervention also surfaced for consideration. Limitations: The issues described in this article are necessarily limited to how they manifested themselves within the context of a particular trial that was conducted in two countries. In addition, other stakeholders may have divergent views on the ethical issues described and may also have identified additional ethical issues that would warrant examination. Conclusions: Adopting similar approaches to addressing ethical issues in future research promises to facilitate this work so that needed strategies to prevent HIV infection among PWIDs can be safely and appropriately tested. Future trials enrolling PWIDs who are at risk of detainment should identify ways of mapping closely their experiences and perceptions in order to better apprehend some of the ethical issues at stake. In addition, scholarly and policy work needs to address the ethical issues related to post-trial access to multi-modal interventions that may be desired by participants, but are not shown to be effective in achieving the primary outcomes of the study.